STRATEGIC HUMAN RESOURCE MANAGEMENT IN INTERNATIONAL BUSINESS: A CASE STUDY OF MULTINATIONAL COMPANIES - Dina Novita; Caroline; Siti Sumiati; Ony Kurniawati; Mohd. Fauzi Hussin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This study delves into Strategic Human Resource Management (SHRM) within the context of international business, utilizing a case study approach to examine the practices of multinational companies. The objective is to shed light on the multifaceted dynamics of HRM in a global context and assess its significance for multinational corporations. The research employs a comprehensive methodology that combines a literature review, qualitative analysis of case studies, and empirical data collection. It examines the role of HRM in multinational companies, emphasizing its crucial function in navigating the complexities of global markets. Furthermore, the study explores the impact of cultural diversity on HRM strategies, recognizing that adequate cross-cultural competence is paramount for success. The case studies offer insights into talent management and recruitment strategies tailored to local markets, emphasizing the adaptability of HR policies to varying international contexts. Moreover, the research underscores the importance of network relationships within and with local partners in shaping HRM outcomes. This study contributes to the field of HRM in international business by integrating existing theories and empirical evidence into a coherent framework. It underscores the need for HRM practices accommodating diverse cultural and institutional contexts. Ultimately, it provides HR professionals and international business leaders with actionable insights to enhance their HRM strategies in the dynamic landscape of global operations.